The relative contributions of anaerobic and aerobic energy supply during track 100-, 400- and 800-m perform - Nevill, A. M.; Ramsbottom, R.; Nevill, M. E.; Newport, S.; Williams, C. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: The present study set out to identify the relative contribution of the laboratory determined physiological measures, (maximal) accumulated oxygen deficit (AOD) and maximal oxygen uptake (.VO2max), when predicting track performance. Methods: Fourteen volunteers (men: n=10; women: n=4); mean (± standard deviation [SD]) height 1.76±0.1 (men) vs 1.62±0.08 m (women); body mass: 67.9±7.1 (men) vs 50.6±8.2 kg (women), ran track races at distances of 100, 400 and 800 m. The individually determined (maximal) AOD and .VO2max were measured under controlled laboratory conditions (68.3±10.2 vs 60.7±16.1; men vs women, mL.O2.Eq.kg-1) and (68.7±7.3 vs 55.6±4.3; men vs women, mL.kg-1.min-1), respectively. Results: Track performance could be predicted using both laboratory measures, AOD and , with a high degree of accuracy: R2=76.9%, 84.8% and 89.1% for 100, 400 and 800 m, respectively. Data analysis confirmed the dominant energy supply during 100-m sprinting was the anaerobic energy supply processes, reflected as AOD. In contrast, oxidative metabolism (reflected as .VO2max) was the dominant source of energy supply during 800-m performance. Conclusion: The results support earlier research, rather than present textbook dogma, namely that aerobic and anaerobic processes contribute equally to maximal exercise lasting approximately 60 s.